Falsework - Wilshere, C. J. (Thomas Telford, 1983)
This guide examines the applications of falsework in projects of all sizes using varied materials. After giving consideration to design concepts and standard solutions, the book concludes with a checklist to help the reader search for potential faults.
Keywords: Scaffolding.; Shoring and underpinning.; elektronické knihy; electronic books